Like, Comment, and Share: Speech-Language Pathologists' Use of Social Media for Clinical Decision Making - Diehm, Emily A.; Hall-Mills, Shannon (Seminars in Speech and Language, 2023)
Many social media sites are dedicated for speech-language pathologists (SLPs); however, the extent to which SLPs utilize them in clinical decision making and evidence-based practice (EBP) is not well understood. The purpose of this study was to explore SLPs' use of traditional and modern resources, including social media, within clinical decision making for assessment and intervention practices. Using a stratified random sampling approach, we invited school-based SLPs in Florida and Ohio and on pediatric-focused, SLP Facebook sites to complete an online survey. The majority (N = 271) reported using social media for professional purposes at least once per week: most frequently Facebook (19–25% of SLPs) or Pinterest (15–18% of SLPs) to learn about new treatment ideas or resources for (12–18%) or read others' summaries of treatment-related research (8–11%), but rarely to pose or answer a clinical question (3–5%). The number of reasons for one's professional social media use was moderately correlated with frequency of social media use, traditional EBP training, and reading a greater number of articles from ASHA and other sources. The results warrant further consideration of how to leverage social media as a tool to increase SLPs' knowledge and implementation of EBP.
Keywords: clinical decision making; schools; SLP; evidence-based practice